2011
DOI: 10.1534/genetics.110.125567
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Enhancer Screen Implicates Sphingolipid Composition in Vacuolar ATPase Function in Saccharomyces cerevisiae

Abstract: The function of the vacuolar H 1 -ATPase (V-ATPase) enzyme complex is to acidify organelles; this process is critical for a variety of cellular processes and has implications in human disease. There are five accessory proteins that assist in assembly of the membrane portion of the complex, the V 0 domain. To identify additional elements that affect V-ATPase assembly, trafficking, or enzyme activity, we performed a genome-wide enhancer screen in the budding yeast Saccharomyces cerevisiae with two mutant assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 65 publications
0
30
0
Order By: Relevance
“…Recently, similar sphingolipid desaturases have been characterized in the diatom T. pseudonana (Michaelson et al, 2013;Tonon et al, 2005). In yeast, and in Arabidopsis, regions within the vacuolar bilayer, enriched in sphingolipids and sterols (Chung et al, 2003;Finnigan et al, 2011), have been identified as essential to the function of vacuolar-ATPases (Ozolina et al, 2013;Yoshida et al, 2013). Vacuolar-ATPases are the proton pumps in plants (reviewed in Martinoia et al, 2007) that provide energy for NO 3 2 transport into the vacuole via NO 3 2 ClC transporters identified in this study.…”
Section: Nitrate Uptake Into the Vacuole A Competitive Advantage In mentioning
confidence: 66%
“…Recently, similar sphingolipid desaturases have been characterized in the diatom T. pseudonana (Michaelson et al, 2013;Tonon et al, 2005). In yeast, and in Arabidopsis, regions within the vacuolar bilayer, enriched in sphingolipids and sterols (Chung et al, 2003;Finnigan et al, 2011), have been identified as essential to the function of vacuolar-ATPases (Ozolina et al, 2013;Yoshida et al, 2013). Vacuolar-ATPases are the proton pumps in plants (reviewed in Martinoia et al, 2007) that provide energy for NO 3 2 transport into the vacuole via NO 3 2 ClC transporters identified in this study.…”
Section: Nitrate Uptake Into the Vacuole A Competitive Advantage In mentioning
confidence: 66%
“…For example, in S. cerevisiae, the proton-pump activity of V-ATPase decreases on deletion of ELO3 or ORM1 and ORM2, all of which are involved in sphingolipid biosynthesis (Chung et al, 2003;Finnigan et al, 2011). In addition, impaired biosynthesis of ergosterol also causes a reduction in V-ATPase activity (Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that deletion of ELO3 or ORM1 and ORM2 causes a reduction in the activity of V-ATPase (Chung et al, 2003;Finnigan et al, 2011). ELO3 is involved in synthesis of very long-chain fatty acids, which are incorporated into sphingolipids (Oh et al, 1997), and ORM1 and ORM2 encode negative regulators of serine palmitoyltransferase, which catalyses the initial step of de novo sphingolipid biosynthesis (Breslow et al, 2010), suggesting a functional connection between sphingolipids and V-ATPase.…”
Section: Loss Of Vacuolar Atpase Causes Drastic Changes Of the Complementioning
confidence: 99%
“…Despite V 1 being the cytoplasmic domain, C26-acyl group-containing sphingolipids are necessary to generate ATPase-competent V 1 domains [82]. Other studies have corroborated genetically the importance of sphingolipids for V-ATPase function [83]. Moreover, luminal acidification of melanocyte trans-Golgi system and endo/lysosomes have been suggested to depend on glycosphingolipids, since a cell line devoid of glucosylceramide synthase presents defective luminal acidification [84].…”
Section: Structure Of V-atpasesmentioning
confidence: 95%